Intelligent Adaptive Routing Algorithm in Software Defined Networks with Quality of Service - Perepelkin, Dmitry; Ivanchikova, Maria (2020 ELEKTRO, 2020)
Currently, the most popular approach in information technology and computer networks is technology of software defined networks (SDN). Its main feature is separation of data plane and control plane levels, as well as support of specified requirements for the quality of service (QoS) of network applications. The aim of this work is the development of intelligent adaptive routing algorithm in SDN with support QoS. Proposed algorithm based on using a composite LARAC metric in that the bandwidth can be constant and the effect of transmission delay varies depending on the control coefficient. To implement the algorithm comparative analysis and experimental research of different neural network architectures were carried out. Also a model that allows the highest accuracy of optimal routes search in SDN with support multiple QoS parameters was developed.